Etika Guru Perspektif Ibnu Saḥnūn Dalam Kitab Ādāb Al-Mu’allimīn - Mega Cahyati; Abdul Halim Sholeh; M. Ubaidillah Al Ghifari; Fajar Syarif (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2022)
The purpose of this research was to determine teacher ethics in the perspective of Ibn Saḥnūn in the book Ādāb al-Mu'allimīn, to analyze teacher ethics in the book, and to analyze the implementation of the concept of teacher ethics according to him in Islamic education today. This research used Grounded Theory method, with a qualitative approach with the type of library research. Sources of data used primary and secondary data sources. Data collection was done by documentation. Analysis of the data used analysis of the content. The results showed that 1). teacher ethics according to Ibn Saḥnn in the Book of Ādāb al-Mu'allimīn there are 18 ethics, including: a). educate sincerely, b).mobilize all their abilities in educating students, c). staying away from differences in treatment of their students, d). be gentle with them, e). provide educational punishment, f). remind them not to play while studying, g). do not punish excessively, h). not burden them with financial problems, i). responsible, j). Prioritize important lessons, k). get them used to doing sunnah practices, l). Pay attention to the development of their manners and morals, m). give advice to them, n). be fair, o). keep themselves busy with writing and adding knowledge, p). Meet their personal needs, q). instilling students' love for Allah, r). maintain the sanctity and cleanliness of the study area. 2) The analysis of teacher ethics in the book is very religious because it is in accordance with the Qur'an and Sunnah, as well as the opinions of scholars, and contains the same elements as those formulated in the National Education Standards, Elucidation of Article 28 paragraph (3 ) point b, and is also in line with the Law on Teachers and Lecturers Chapter 3 Article 7 concerning the principle of teacher professionalism. 3). According to him, the implementation of the concept of teacher ethics in Islamic education today can be implemented in educational institutions in five stages, namely: a). preparation stage, b). planting stage, c). growth stage, d). development stage, and e). guard stage.